Masculinities and the contemporary Irish theatre - Singleton, Brian (Performance interventions., 2011)
Irish theatre critic Helen Meany once said that she had seen so many father/son relationships in Irish theatre that she almost believed she might have had one herself! And so it is that Irish theatre and its histories appear to be dominated by men and their actions. However, close readings of a variety of performative encounters in Ireland in the past two decades and more do not point to a performance of a dominance by men. Socially and culturally contextualized performance analysis in this book reveals masculinities that are anything but hegemonic, played out in the theatres and other arenas of performance all over Ireland. These masculinities are not necessarily white, straight, Catholic and middle-class. In fact, many of them fall between the cracks in the edifice of dominance because of their class, race, religion and sexuality, while some contest culturally the performance of patriarchy in Irish society. And there are many that, until now, have been excluded from the narratives of Irish theatre history altogether. This timely book features first-hand performance analyses to deconstruct the masculinities represented on the Irish stage from the early 1990s right up to the present day.